Digital Supply Chain and its impact on the competitiveness of economy in countries and regions - Irina Volkova; Anna Mikhaylova; Marina Shevchenko (International Journal of Supply Chain Management, 2020)
Abstract—The study considers the effect of digitalization on the international competitiveness of the global supply chain and individual countries in the future, as well as the material well-being of people. The purpose of the study is to analyze current trends in the development of digital supply chain and its impact on the competitiveness of individual countries. The research is based on the methods of comparative analysis, systematic approach and correlation. Based on the analysis of the research results, it was found that digitalization has a significant impact on the international competitiveness of the economy, as well as the material well-being of people. The influence of the development level of information and communication technologies (ICT) on global competitiveness is studied through the example of 3 economies with different digitalization levels - Russia, Azerbaijan, and Switzerland. The current level of digitalization of supply chain in Russia in comparison with other countries has been analyzed. The research results are of particular scientific and practical value for assessing the global competitiveness of the country; the study also identifies the problems and prospects of supply chain digitalization.